IMPACT OF NANO-CONVENTIONAL NPK FOLIAR APPLICATION AND ROW DISTANCE ON SOME GROWTH AND CHEMICAL TRAITS OF SUNFLOWER (HELIANTHUS ANNUUS L.) - J. J. Hashim; S. A. Kakarash (مجلة الأنبار للعلوم الزراعية)
Sunflower cultivars are widely cultivated for their oil-rich seeds and ornamental value, making them a staple crop in many agricultural regions. To enhance sunflower plant growth and maximize crop yield, companies and farmers commonly utilize fertilizers containing nitrogen, phosphorus, and potassium. This study explored the effect of different levels of NPK fertilizers, including nano-conventional NPK foliar applications at two stages 30 and 55 days after planting and two row distance (50, 70 cm) on the growth and chemical traits of sunflower using a factorial experimental design within a Randomized Complete Block Design (RCBD) with three replicates. Data collected was analyzed to determine the growth parameters and chemical components of the sunflower. The study found that the recommended soil NPK fertilizer significantly affected all the growth parameters which included the highest value for chlorophyll content (38.73 and 36.48 SPAD), leaf area (3984.43 and 3912.09 cm2), dry matter (102.94 and 131.16 g plant-1). Nano NPK foliar application at different levels showed positive and significant effects on chlorophyll content, leaf area, and dry matter weight. Nitrogen (N), phosphorus (P), and potassium (K) content in the leaves also increased with nano NPK application in 2022 at 1.679%, 0.432%, and 1.281%. The highest level of N, P and K were recorded from conventional NPK at 0.513%, 0.369%, and 0.462%, respectively in 2021. On the other hand, the lowest values for most of the studied traits were recorded for the control treatment.Higher levels of conventional NPK foliar applications resulted in increased growth parameters and nutrient content. The impact of conventional NPK foliar applications was more pronounced compared to nano NPK application. Data collection at different stages revealed variations in growth and nutrient accumulation over time.